Epicatechin gallate, a naturally occurring polyphenol, alters the course of infection with β-lactam-resistant Staphylococcus aureus in the zebrafish embryo - Stevens, Christina S.; Rosado, Helena; Harvey, Robert J.; Taylor, Peter W. (Frontiers in Microbiology, 2015)
(-)-epicatechin gallate (ECg) substantially modifies the properties of Staphylococcus aureus and reversibly abrogates β-lactam resistance in methicillin/oxacillin resistant (MRSA) isolates. We have determined the capacity of ECg to alter the course of infection in zebrafish embryos challenged with epidemic clinical isolate EMRSA-16. At 30 hours post fertilization (hpf), embryos were infected by injection of 1-5 × 103 colony forming units (CFU) of EMRSA-16 into the circulation valley or yolk sac. Infection by yolk sac injection was lethal with a challenge dose above 3 × 103 CFU, with no survivors at 70 hpf . In contrast, survival at 70 hpf after injection into the circulation was 83% and 44% following challenge with 3 × 103 and 1-5 × 103 CFU respectively. No significant increases in survival were noted when infected embryos were maintained in medium containing 12.5-100 µg/mL ECg with or without 4 or 16 µg/mL oxacillin. However, when EMRSA-16 was grown in medium containing 12.5 µg/mL ECg and the bacteria used to infect embryos by either the circulation valley or yolk sac, there were significant increases in embryo survival in both the presence and absence of oxacillin. ECg-modified and unmodified, GFP-transformed EMRSA-16 bacteria were visualized within phagocytic cells in the circulation and yolk sac; pre-treatment with ECg also significantly increased induction of the respiratory burst and suppressed increases in IL-1β expression typical of infection with untreated EMRSA-16. We conclude that exposure to ECg prior to infection reduces the lethality of EMRSA-16, renders cells more susceptible to elimination by immune processes and compromises their capacity to establish an inflammatory response in comparison to non-exposed bacteria.